DAUR ULANG SAMPAH ORGANIK DENGAN TEKNOLOGI VERMICOMPOSTING - Wahyono, Sri (Jurnal Teknologi Lingkungan, 2001)
Organic material from municipal solid wastes can be recycled by compostingtechnology become organic fertilizer. One kind of composting technologies isvermicomposting that use earthworm as ‘machine” of composting process. Thereare two products from the process: biomass of worm and casting. Vermicomposting consists of three phases of activities such as preparation,processing, and nursing phase. Preparation phase consists of choosing oflocation, system, building, and equipment. Processing phase consists of making of worm media, preparation of worm and planting. Nursing phase consists of feeding, turning, cropping of casting and controlling of the disease. This article talk about those phases and the classification and characterization of earthworm.